Region-Based Plant Vegetation Productivity in Cibinong Botanical Garden, Bogor Regency - Chairul Chairul; Sunardi Sunardi; Senriella Habinuya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Vegetation productivity in botanical gardens plays a crucial role in carbon sequestration and soil nutrient regulation, yet region-based differences in vegetation performance under ex situ conservation systems remain poorly understood. This study aims to analyze vegetation composition and structure, estimate biomass and carbon stock, and evaluate the influence of dominant species on soil nutrient content across different regional collections in the Cibinong Botanical Garden, Bogor Regency. The research was conducted in seven regional collections (Java–Bali, Sumatra, Kalimantan, Sulawesi, Maluku, Nusa Tenggara, and Papua) using a survey method with 20 × 50 m plots. Tree biomass was estimated using allometric equations, while carbon stock was calculated based on organic carbon content. Soil chemical properties, including organic carbon and phosphorus, were also analyzed. The results showed that the Kalimantan region had the highest biomass and carbon stock, reaching 237.26 tons/ha and 111.51 tons/ha, respectively, largely influenced by the dominance of Pentace sp. In contrast, the Maluku region exhibited the highest soil organic carbon and available phosphorus, despite having lower biomass values. These findings indicate that vegetation productivity is not solely determined by biomass accumulation, but also by species composition, stand structure, and soil nutrient dynamics. This study highlights the importance of region-based vegetation management in botanical gardens to optimize carbon storage and maintain soil fertility under ex situ conservation systems.